Penentuan Alternatif Strategi Pemasaran dengan Pendekatan Analisis SWOT melalui Faktor Internal dan Faktor Eksternal pada Peningkatan Pendapatan UMKM KUBE (Kelompok Usaha Bersama) Mega Buana di Masa Pandemi Covid - 19 - Ayu Feranika; Despita Meisak; Laura Prasasti; Masgo Masgo; Gita Melati (Sekolah Tinggi Ilmu Ekonomi Indonesia (STEI) Jakarta, 2022)
This study aims to analyze the marketing strategy of Kube Mega Buana UMKM and analyze the application of accounting information systems to increase the income of Kube Mega Buana UMKM during the covid 19 pandemic. This type of research is quantitative and qualitative descriptive with data collection techniques, namely observations, interviews, literature studies, and distributing questionnaires with a total sample of 25 respondents who are members of Kube Mega Buana UMKM for strategy assessment. The results of this study indicate that Kube Mega Buana is in Quadrant I position with values ​​(X = 1.44) and (Y = 1.23) which explains that UMKM Kube Mega Buana has great opportunities and strengths so that they can take advantage of existing opportunities with a value of The highest coordination of S-O strategy was 4.71, with alternative strategies produced, namely innovating pineapple products and packaging forms, maintaining relationships with partners, utilizing digital marketing technology advances in marketing, and maintaining the quality of raw materials.